Late-Stage C–H Deuteration of Organic Compounds via Ligand-Enabled Palladium-Catalyzed Hydrogen Isotope Exchange - van Gemmeren, Manuel; Beller, Matthias (Synlett, 2024)
Manuel van Gemmeren was born in Madrid (Spain) and raised in both Spain and Germany. After studying chemistry at the Albert-Ludwigs University in Freiburg until 2010, he conducted his doctoral studies in the lab of Prof. Benjamin List and obtained his doctorate in 2014 (summa cum laude). Subsequently, he joined the group of Prof. Rubén Martín for postdoctoral studies. From 2016 onwards, he established his independent research group at the University of Münster. In 2022, he joined the Otto Diels Institute of Organic Chemistry at Kiel University as a tenured professor of organic chemistry. Research in the van Gemmeren lab focusses on the development of novel synthetic methods, typically based on Pd-catalyzed C–H activation, that enable challenging transformations to proceed with catalyst-controlled reactivity and selectivity.Matthias Beller was born 1962 in Gudensberg (Germany) and studied chemistry at the University of Göttingen, Germany, where he completed his Ph.D. in 1989 in the group of Prof. L.-F. Tietze. As recipient of a Liebig scholarship, he subsequently spent one year studying with Prof. K. B. Sharpless at MIT, USA. From 1991 to 1995 he worked in industry. He then moved to the Technical University of München as a professor of inorganic chemistry. In 1998, he relocated to Rostock to head the Institute for Organic Catalysis, which in 2006 became the Leibniz Institute for Catalysis. The work of his group has been published in nearly 1150 original publications and reviews, and over 150 patent applications have been filed.
Keywords: isotopic labeling; late-stage functionalization; imaging; synthetic methods; catalysis